2019
DOI: 10.3390/d11050084
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Isotopic Turnover for Understanding Key Aspects of Animal Ecology and Nutrition

Abstract: Stable isotope-based methods have proved to be immensely valuable for ecological studies ranging in focus from animal movements to species interactions and community structure. Nevertheless, the use of these methods is dependent on assumptions about the incorporation and turnover of isotopes within animal tissues, which are oftentimes not explicitly acknowledged and vetted. Thus, the purpose of this review is to provide an overview of the estimation of stable isotope turnover rates in animals, and to highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 126 publications
(207 reference statements)
1
36
0
Order By: Relevance
“…Carbon (δ 13 C) and sulfur (δ 34 S) isotope data help elucidate the production sources responsible for the energy flow in the food web, while nitrogen (δ 15 N) suggests the relative trophic position at which an animal is feeding (Connolly, Guest, Melville, & Oakes, 2004;Croisetière, Hare, Tessier, & Cabana, 2009;Minagawa & Wada, 1984;Pinnegar & Polunin, 1999). Different animal tissues have different turnover rates (Tieszen, Boutton, Tesdahl, & Slade, 1983) with fast turnover tissues (e.g., plasma or liver) representing short-term diet while slow turnover tissues (e.g., muscle) represent long-term diet (Carter, Bauchinger, & McWilliams, 2019). Consequently, muscle tissue can help identify consistent patterns in predator resource use (Carter et al, 2019;Vander Zanden, Clayton, Moody, Solomon, & Weidel, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon (δ 13 C) and sulfur (δ 34 S) isotope data help elucidate the production sources responsible for the energy flow in the food web, while nitrogen (δ 15 N) suggests the relative trophic position at which an animal is feeding (Connolly, Guest, Melville, & Oakes, 2004;Croisetière, Hare, Tessier, & Cabana, 2009;Minagawa & Wada, 1984;Pinnegar & Polunin, 1999). Different animal tissues have different turnover rates (Tieszen, Boutton, Tesdahl, & Slade, 1983) with fast turnover tissues (e.g., plasma or liver) representing short-term diet while slow turnover tissues (e.g., muscle) represent long-term diet (Carter, Bauchinger, & McWilliams, 2019). Consequently, muscle tissue can help identify consistent patterns in predator resource use (Carter et al, 2019;Vander Zanden, Clayton, Moody, Solomon, & Weidel, 2015).…”
mentioning
confidence: 99%
“…Different animal tissues have different turnover rates (Tieszen, Boutton, Tesdahl, & Slade, 1983) with fast turnover tissues (e.g., plasma or liver) representing short-term diet while slow turnover tissues (e.g., muscle) represent long-term diet (Carter, Bauchinger, & McWilliams, 2019). Consequently, muscle tissue can help identify consistent patterns in predator resource use (Carter et al, 2019;Vander Zanden, Clayton, Moody, Solomon, & Weidel, 2015).…”
mentioning
confidence: 99%
“…Both plasma glucose and plasma 13 C allocation showed the expected pattern of one marked peak 6 h post-prandial, in agreement with that reported by Felip et al (2013 , 2015 ) using a stable isotope post-feeding trial, or by Montoya et al (2010) and Gómez-Milán et al (2011) , who analysed plasma glycaemia performance after ingesta. Moreover, both lower levels (<1%) of total stable isotope allocation per g of ingested isotopes confirmed that plasma does not act as a final fate but rather a transitory pathway with a fast turnover ( Carter et al, 2019 ). 15 N allocation to the liver also corresponded to reports in previous studies by Beltrán et al (2009 ) and Felip et al (2012 , 2015) for gilthead sea bream after a force-fed meal.…”
Section: Discussionmentioning
confidence: 82%
“…It has generally been reported that in addition to the inherent differences in between animal- and plant-protein based diets 25 , animal protein diets tend to show low DTDFs and high assimilation rates, whereas plant protein diets are usually associated with high DTDFs 29 , 50 . This is because animal protein diets are assumed to readily satisfy the amino acid requirements of consumers, resulting in both the protein and lipid content of consumer tissues being closely matched to those of their diets 64 , 66 . In contrast, the amino acids from plant protein diets are often different, and usually undergo different metabolic pathways, such as the transamination of keto acids from the carbohydrates in order to satisfy the specific amino acid requirements for consumer animals 67 .…”
Section: Discussionmentioning
confidence: 99%